Synthesis of mannich bases of 4-hydroxyacetophenone - Wan Nor Asmariati Wan Hasan, 1994- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2017